Retos que se presentan a la ciudad de Medellín para aplicar la contabilidad ambiental - Correa Ochoa, Dora Luz (Correa, D., (2019). Retos que se le presentan a la ciudad de Medellín para aplicar la Contabilidad Ambiental (Trabajo de grado Contaduría Pública). Universidad de San Buenaventura Colombia, Facultad de Ciencias Empresariales, Medellín, 2019)
This research work is developed with the purpose of analyzing the challenges that the city of Medellín may face in terms of the application of environmental accounting. For this, it is necessary to adopt a management system that minimizes this problem; it is there, where the discipline of environmental accounting, as the appropriate mechanism to create socio-environmental policies in organizations, in a way that diminishes the impact of industrial processes, bringing challenges to identify costs, benefits, and technological investment, which facilitates the management of environmental accounts in productive activities. Regarding the methodology, the qualitative approach with descriptive scope and the design of a documentary analysis was used, where the ideas that make up the methodology of environmental accounting were expanded, to create social awareness in the business sector. This will expose the actions for the prevention and improvement of the environmental crisis, through the tools of this discipline, being environmental accounting the appropriate means to determine the costs incurred in the efforts for the ecological balance, with the management appropriate waste, solid waste and its final destination; avoid being polluting agents, and see reflected business actions with the commitment to care for the environment, thus complying with the required regulations and regulations that must be implemented in environmental policy, enabling the management of sustainable development and create corporate social awareness.